2021
DOI: 10.1126/science.abc8697
|View full text |Cite
|
Sign up to set email alerts
|

Targeting a neoantigen derived from a common TP53 mutation

Abstract: TP53 (tumor protein p53) is the most commonly mutated cancer driver gene, but drugs that target mutant tumor suppressor genes, such as TP53, are not yet available. Here, we describe the identification of an antibody highly specific to the most common TP53 mutation (R175H, in which arginine at position 175 is replaced with histidine) in complex with a common human leukocyte antigen–A (HLA-A) allele on the cell surface. We describe the structural basis of this specificity and its conversion into an immunotherape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
204
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(212 citation statements)
references
References 83 publications
7
204
0
1
Order By: Relevance
“…Since p53 mutations do not occur in normal, healthy cells, they might serve as tumor-specific neoantigens. As anti-p53 antibodies have been detected in cancer patients (including patients with CRC) and antibodies and T-cell receptors can recognize p53 mutants, vaccines targeting mutant p53 are being evaluated in clinical trials for the treatment of many different types of cancer, including CRC [ 194 , 195 , 196 , 197 , 198 ]. Unfortunately, clinical studies with p53 vaccines so far have not shown convincing results.…”
Section: P53 As a Therapeutic Targetmentioning
confidence: 99%
“…Since p53 mutations do not occur in normal, healthy cells, they might serve as tumor-specific neoantigens. As anti-p53 antibodies have been detected in cancer patients (including patients with CRC) and antibodies and T-cell receptors can recognize p53 mutants, vaccines targeting mutant p53 are being evaluated in clinical trials for the treatment of many different types of cancer, including CRC [ 194 , 195 , 196 , 197 , 198 ]. Unfortunately, clinical studies with p53 vaccines so far have not shown convincing results.…”
Section: P53 As a Therapeutic Targetmentioning
confidence: 99%
“…Recently, Han-Chung Hsiue E. et al published an interesting study where the most common TP53 mutant R175H (in which arginine at position 175 is replaced with histidine) was targeted with a bispecific antibody (H2) [ 197 ]. The highly specific antibody binds to human leukocyte antigen-A (HLA-A) allele on the cell surface, which presents peptide fragments of the TP53 R175H mutant, while its other domain binds to a T-cell receptor to trigger an antitumor response.…”
Section: P53 As a Druggable Targetmentioning
confidence: 99%
“…They have developed a specific bispecific single-chain diabody (SCDB) antibody that targets TP53 and RAS mutations. This bispecific antibody can specifically recognize and activate T cells in vitro and in mice, exerting good anti-tumour effects without cross-reactivity and with a good safety profile (91,92).…”
Section: Advances In the Study Of Neoantigensmentioning
confidence: 99%